Writing in brazilian language teacher education: Possible advances in future teachers’ language capacities development - Ascencio Miquelante, Marileuza; Lopes Cristovão, Vera Lúcia (Calidoscópio, 2023)
This research is related to foreign Language Teacher Education based on the study of genres. It aims at investigating the types of correction used by the teacher-researcher and their role in the development of future teachers’ language capacities through writing taken as social action. It is grounded on Socio-discursive Interactionism and the procedure of didactic sequence. The data collecting was constituted by three versions of a Comment written by a future teacher in the English Language III course, during the implementation of a Didactic Sequence and the teacher-researcher’s correction types on their texts. The data analysis techniques were based on the identification of the correction types and the language capacities. Considering the three steps of writing in the didactic sequence implemented: i. initial production; ii. revising and rewriting; iii. final production and the correction types identified, this investigation presents an alternative to provide future teachers with a unique experience that can contribute to the process of English learning as well as to the student’s language capacities development. Keywords: Teacher education; Study of genres; Writing.